El óxido crómico como indicador externo para estimar producción fecal y consumo en las pruebas de digestibilidad - Iturbide C, A. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Although the majority of the authors consulted agreed that the use of chromic is presented. Some of the factors that may influence the validity of the fecal output and consumption estimations with this indicator are discussed. Although the majority of the authors consulted agreed that the use of chromic oxide is practical and reliable, it is stressed that unless the factors affecting its use are previously considered and evaluated for each locality and animal specie, the estimations obtained with this indicator may be seriously biased.